National self-consciousness and cultural resistance in Susan Abulhawa's Against the Loveless World: A postcolonial study - Mohammed, Muntadhar Ali; Amjad, Fazel Asadi (Research Journal in Advanced Humanities, 2025)
The present study intends to examine national self-consciousness and cultural resistance in Susan Abulhawa's Against the Loveless World (2020). It shows that the colonizers' arrival in Palestine resulted in the deterioration of its culture and led to the subsequent oppression of its people. On the other hand, the current study shows that the selected novels serve as a means of keeping alive the memory of the Palestinians' national self-consciousness in their struggle against colonial Zionism and a literary act that embodies cultural resistance. It also examines the rise of Palestinian characters to the status of national icons, which parallels the heroic history of the Palestinians and their ongoing struggle for independence. The theoretical analysis of this research is based on the work of postcolonial theorist Edward Said and is set within the context of Postcolonial theory. In addition, the research delves into additional aspects of postcolonial reading by demonstrating how the harsh and chaotic socioeconomic and political realities of colonial Palestine are counterproductive to the ideal national self-consciousness of the characters, as well as how the depressed , ambitious rural people of Palestine are heavily influenced by the tragic repercussions of war, becoming disillusioned and marginalized. It also observes the chosen works' political-historical context as well as the characters' realization of the current situation as they bear witness to the decline of their own country and their efforts to preserve their cultural legacy and identity. Ultimately, this study demonstrates that the cultural and identity crisis of colonial Palestine leads to growth in cultural resistance and national self-consciousness and allows characters to confront the leading edge of oppressive forces